Catalytic Conjunctive Coupling of Carboxylic Acid Derivatives with 9‐BBN‐Derived Ate Complexes. (4th April 2019) - Law, Chunyin; Meng, Yan; Koo, Seung Moh; Morken, James P.
Abstract: β‐Boryl carbonyl compounds are produced by a Ni‐catalyzed cross‐coupling of vinylboron "ate" complexes and acid chloride or acid anhydride electrophiles. The reactions are efficient, being complete in as little as two minutes, and can be applied to a broad range of substrates. Abstract : Kuppeln im Konjunktiv : Eine neue Route zu nützlichen β‐Borylcarbonylverbindungen fußt auf der Ni‐katalysierten Addition von Alkenylboron‐„At"‐Komplexen an aktivierte Carbonsäuren. Die Reaktionen sind effizient – sie laufen innerhalb von nur zwei Minuten vollständig ab – und lassen sich auf vielfältige Substrate anwenden.